Use of remdesivir for patients with Covid-19: a review article - Azevedo,Thomás Cavalcanti Pires de (2020)
SUMMARY The etiological agent of COVID-19, which causes severe respiratory diseases such as pneumonia and pulmonary insufficiency, has been confirmed as a new coronavirus, now known as Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2). There is currently no authorized medication for the treatment of COVID-19. No vaccines have been authorized. Thus, this study aimed at conducting a review of the use of Remdesivir in patients with COVID-19. The following electronic databases were used MEDLINE, SCIELO, LILACS, and PUBMED. On May 1, Remdesivir received emergency use authorization from the Food and Drug Administration. Remdesivir is currently the most promising molecule in the treatment of COVID-19, taking into account its broad antiviral spectrum (considering the genetic sequences of the virus, it is expected to maintain activity against SARS-CoV-2). There is in vitro and in vivo information available for coronaviruses, as well as an extensive clinical safety database (from a clinical trial of the Ebola virus and in the context of the Monitored Emergency Use of Unregistered and Investigational Interventions - MEURI). Further studies are relevant as available data on the efficacy and safety of Remdesivir against SARS-nCoV-2 are limited.